2018
DOI: 10.1177/0021998318768390
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of mechanical and electrical properties with processing variables in MWCNT reinforced thermoplastic nanocomposites

Abstract: The influence of the processing variables and nanotube content on the mechanical and electrical properties of Polyamide 6,6-based nanocomposites reinforced with Multi-Walled Carbon Nanotubes (MWCNTs) is investigated. Results show that variation in the processing variables such as compounding method, injection melt temperature, injection speed, mold temperature, and holding pressure varies the properties significantly. In fact, composites containing similar contents of the nanofillers show variations in mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…However, while their aspect ratios provide larger interfacial regions leading to enhancement of the properties, their processing is challenging. In fact, achieving dispersed or aligned nanofillers requires effective prior investigations [8,9,25]. Results showed that incorporation of 4 vol.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, while their aspect ratios provide larger interfacial regions leading to enhancement of the properties, their processing is challenging. In fact, achieving dispersed or aligned nanofillers requires effective prior investigations [8,9,25]. Results showed that incorporation of 4 vol.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Recent advancements in technology demand for novel electrically and/or thermally conductive multifunctional plastics with the potential to be fabricated precisely, and through mass manufacturing processes. Incorporation of various conductive fillers such as metals fibers, carbon black, carbon fibers, and low melting alloys in the polymers to create a conductive network within a polymeric base has been one of the attempts toward this target [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations